Probing free-carrier recombination in silicon strip nano-waveguides - Aldaya, Ivan [UNESP]; Gil-Molina, Andres; Pita, Julian L.; Gabrielli, Lucas H.; Fragnito, Hugo L.; Dainese, Paulo; IEEE (Ieee, 2018)
We analyze recombination dynamics of photo-generated free-carriers in strip silicon nanowaveguides, revealing a highly nonlinear decay dynamics with a time-dependent lifetime ranging from similar to 800 ps at the beginning to similar to 300 ns at the end of the decay.